2008
DOI: 10.1126/science.1155939
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Stratospheric Ozone Recovery on the Southern Hemisphere Westerly Jet

Abstract: In the past several decades, the tropospheric westerly winds in the Southern Hemisphere have been observed to accelerate on the poleward side of the surface wind maximum. This has been attributed to the combined anthropogenic effects of increasing greenhouse gases and decreasing stratospheric ozone and is predicted to continue by the Intergovernmental Panel on Climate Change/Fourth Assessment Report (IPCC/AR4) models. In this paper, the predictions of the Chemistry-Climate Model Validation (CCMVal) models are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

31
322
2
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(356 citation statements)
references
References 17 publications
31
322
2
1
Order By: Relevance
“…If, as recently suggested [Son et al, 2008], ozone depletion is the primary cause of wind speed increases, then this cloud forcing acts as a positive feedback on the ozone induced cooling. It more than doubles the negative radiative forcing from stratospheric ozone loss and suggests that future ozone recovery would cause a positive radiative forcing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If, as recently suggested [Son et al, 2008], ozone depletion is the primary cause of wind speed increases, then this cloud forcing acts as a positive feedback on the ozone induced cooling. It more than doubles the negative radiative forcing from stratospheric ozone loss and suggests that future ozone recovery would cause a positive radiative forcing.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of SH climate shows significant changes in the Southern Annular Mode over recent decades [Thompson and Solomon, 2002;Son et al, 2008]. These changes have been attributed mainly to stratospheric ozone loss [Yang et al, 2007] but also to increases in greenhouse gases [Fyfe et al, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Perlwitz et al [2008] and Son et al [2008] demonstrated the advantage of using coupled chemistry climate models (CCMs) to simulate the impacts of stratospheric ozone changes on the circulation of the Southern Hemisphere. CCMs are relatively new tools that include global dynamics and radiation as well as fully interactive stratospheric ozone chemistry, thereby simulating both ozone's influence on the atmospheric circulation and the circulation's (including transport of ozone from midlatitudes) influence on ozone concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Because the ventilation of SAMW and CDW occurs on decadal and longer time scales, a lag between peak ozone forcing and maximum changes in ocean ventilation is expected (9). As stratospheric ozone recovers over the next 40 to 60 years, the recent trend of intensifying summer westerly winds may slow or reverse (6,27,28). However, continued increases in greenhouse gases will likely lead to strengthened westerlies during other seasons.…”
mentioning
confidence: 99%